Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1155/2016/7235984
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous WiFi Sensor for Heating Systems in the Internet of Things

Abstract: In smart cities and home applications, the use of Wireless Sensor Networks to extract environmental data becomes more common with the passing of time. These sensors are used for a wide array of applications, but mainly to manage energy consumption in domestic buildings. One of the key energy consumers in households is heating systems. To monitor them, sensors are used with wireless communication protocols, like ZigBee, to transmit data to a central processing unit (CPU). WiFi communications, on the contrary, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This amount of harvested energy adds to the battery and prolongs its operational lifetime. For instance, the waste heat from a central heating installation, can extend the operational lifetime of the batteries in a monitoring system powered based on a WiFi communication technology [ 141 ]. Based on the size of the solar cells and the amount of illumination of the sun, solar energy harvester modules can keep devices powered by extending the battery’s lifetime, which operate under LPWAN technologies [ 139 ].…”
Section: Energy Harvesting Solutions For Iot Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This amount of harvested energy adds to the battery and prolongs its operational lifetime. For instance, the waste heat from a central heating installation, can extend the operational lifetime of the batteries in a monitoring system powered based on a WiFi communication technology [ 141 ]. Based on the size of the solar cells and the amount of illumination of the sun, solar energy harvester modules can keep devices powered by extending the battery’s lifetime, which operate under LPWAN technologies [ 139 ].…”
Section: Energy Harvesting Solutions For Iot Technologiesmentioning
confidence: 99%
“…Experimental analyses in literature on the suitability of specific energy harvesters with IoT technologies[139,[141][142][143][144].…”
mentioning
confidence: 99%
“…As some of these devices require mobility, they must be battery-powered, and their battery lifespan is an issue that needs to be addressed accordingly. While thermoelectric energy harvesting was used to build autonomous WiFi sensors for a heating system [12], it has also been shown that multiple years of battery lifetime are possible for WiFi sensors, in the case of periodic data transmission at high data rates [13]. This corresponds with the principle of device hibernation already supported by the specialized IoT technologies [2]- [4].…”
Section: Related Workmentioning
confidence: 99%
“…Internet of Things (IoT) devices have become ubiquitous in a wide range of areas, including Industry 4.0, smart homes, smart cities, healthcare systems, the automotive sector, public services, and critical infrastructure [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The anticipated deployment of future generations of mobile access [ 10 ] and Low-Power Wide Area Networks (LPWAN) [ 11 ] technologies will see greater investment and drive the evolution of the IoT ecosystem [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%